Endosperm-based postzygotic hybridization barriers in Arabidopsis and Capsella - Ali, Mohammad Foteh (SLU/Dept. Of Plant Biology, 2021)
In Arabidopsis, endosperm development is very important for viable seed development. Especially, endosperm cellularization is a crucial event for embryo survival and if it fails, can lead to embryo arrest, as observed in seeds derived from interploidy and interspecies hybridization. In case of interploidy crosses, increased ploidy level creates genome dosage imbalance in endosperm and in case of different species, a similar dosage imbalance basis is suspected, but remains to be broadly established. In this study, we investigated the viability of hybrid seeds between two outbreeding species, Arabidopsis lyrata and A. arenosa, in relation with the development of their endosperm. A. lyrata × A. arenosa (Female × Male) hybrid seeds were shrivelled, dark brown and inviable, with delayed endosperm cellularization. In contrast, A. arenosa × A. lyrata produced tiny inviable seeds with precocious endosperm cellularization. We also investigated if similar mechanisms could exist between different populations of the same species A. lyrata. In case of intraspecies crosses, A. lyrata Austrian population, when used as seed plant, produced tiny seeds and when used as pollen donor, produced shrivelled dark brown aborted seeds. However, no differences in endosperm cellularization were identified. According to our results, we propose that the hybridization barrier observed between A. lyrata and A. arenosa and between A. lyrata populations is a consequence of different levels of parental conflict experienced by the mating partners. Finally, the genetic analysis of A. arenosa and A. lyrata hybridization barrier suggests that cross direction-dependent multiple loci are responsible for the non-reciprocal hybrid seed defects we observed.